Penerapan Metode Hafalan Syair pada Kitab Matn Al-Ajurumiyah dalam Mengatasi Kesulitan Belajar Nahwu pada Siswa - Habibur Rahman; Muhammad Yusron Maulana El-Yunusi (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
Naḥwu as a tool for reading book texts, is a tool or key to understanding the contents of Arabic texts. However, until now many pesantren-based madrasah students have difficulty understanding naḥwu science. This study intends to analyze the method of memorizing poetry in the book of Matn al-Ajurumiyah in overcoming the difficulties of learning naḥwu in students at Darut Tauhid Islamic Boarding School Kenjeran Surabaya. The type of research used was field research with a qualitative descriptive approach. Methods of data collection carried out by the method of observation, interviews, and documentation. This study found that in overcoming the difficulties of learning nahwu, Islamic boarding schools apply the sorogan method, to train students to get used to reading Arabic books independently in front of the teacher, the bandongan method is based on reading the book and information from the teacher, the rote method, always remembering the lessons that have been taught later applied when reading the book. Furthermore, the teacher changes the sentences in the book of Matn al-Ajurumiyah which are in the form of Arabic and Nastar, into poetry sentences in Indonesian.